Enhanced recovery concepts in paediatric patients who underwent appendectomy: a retrospective cohort study at a tertiary university hospital. Issue 2 (February 2023) - Al-Taher, Raed; Alshahwan, Hebah; Abdelhadi, Saja; Abeeleh, Farah Abu; Rashdan, Mohammad; Amarin, Marzouq; Addasi, Rami; Alsaraireh, Doha; Abu-shanab, Ahmad; Alaridah, Nader
Objective: To investigate if the implementation of enhanced recovery after surgery (ERAS) pathways could be effective in paediatric patients undergoing appendectomy. Methods: This retrospective study analysed the data from patients aged ≤18 years that underwent appendectomies. The data collected included age, sex, application of enhanced recovery concepts (ERCs) and clinical outcomes. Results: A total of 93 paediatric patients were retrospectively categorized into two groups: patients in group 1 did not experience the use of ERCs during their appendectomies; and patients in group 2 had ERCs applied during their appendectomies. Patients in both groups were exposed to some elements of ERAS, including preoperative patient/parent counselling, limited fasting durations, antibiotic prophylaxis and no bowel preparations. Duration of hospital stay was significantly longer in group 1 compared with group 2 (3.47 ± 1.81 days versus 2.24 ± 1.52 days, respectively. There were no significant differences between the two groups in term of postoperative pain control, hospital cost, readmissions, reoperations and emergency room visits. Conclusion: Implementing ERCs in paediatric patients undergoing appendectomies provided a significant improvement in patient recovery with a shorter hospital stay, with no increase in postoperative pain, hospital cost, rate of readmission and reoperation.